PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA PT. BANK ACEH DI KOTA BANDA ACEH - Yuliana Yuliana; Yulfrita Adamy; Fakhrurrazi Abbas; Arie Yulistio (Politeknik Negeri Lhokseumawe, 2019)
Abstract: The purpose of this study was to determine the effect of service quality provided by employees on customer loyalty at PT. Bank Aceh, and to find out which dominant factors influence customer loyalty at PT. Bank Aceh. This research was conducted at PT. Bank Aceh with the object of research on service quality towards customer loyalty, while the subject of this research is all customers of PT. Bank Aceh totaling 100 people, using a multiple linear regression analysis model. The results showed that reliability (x1), responsiveness (x2), confidence (x3), empathy (x4) and realization (x5) with the dependent variable of customer loyalty obtained a correlation coefficient of 85.4%. Then based on the results of the coefficient of determination, it is explained that there is a strong influence between the reliability variable (x1), responsiveness (x2), confidence (x3), empathy (x4) and manifestation (x5) to increase customer loyalty of PT. Bank Aceh in Banda Aceh City, with a determination coefficient value of 73.0%. While partially the variables that have a dominant influence are the responsiveness variables and the manifestation variables given by the PT. Bank Aceh in Banda Aceh City, because the regression coefficient value is greater than the other variable regression coefficient values. Keywords: Service Quality and Customer Loyalty